Optimization of fermentation conditions for the production of curcumin by engineered Escherichia coli - Couto, Márcia R. (2017)
Curcumin is a plant secondary metabolite with outstanding therapeutic effects. Therefore, there is a great interest in developing new strategies to produce this high-value compound in a cheaper and environmentally friendly way. Curcumin heterologous production in E. coli using artificial biosynthetic pathways was previously demonstrated using synthetic biology approaches. However, the culturing conditions to produce this compound were not optimized and so far only a two-step fermentation involving the exchange of the culture medium allowed to obtain high concentrations of curcumin, which limits its production at an industrial scale. In this study, the culturing conditions to produce curcumin were evaluated and optimized. In addition, it was concluded that E. coli BL21 allows to produce higher concentrations compared to E. coli K-12 strains. Different IPTG concentrations, time of protein expression induction and substrate type and concentration were also evaluated. The highest curcumin production obtained was 959.3 µM (95.93% of percent yield), which was 3.1-fold higher than the highest concentration previously reported. This concentration was obtained using a two-stage fermentation with LB and M9. Moreover, TB demonstrated to be a very interesting alternative medium to produce curcumin since it also led to high concentrations (817.7 µM). The use of this single fermentation medium represents an advantage at industrial scale and although the final production is lower than the one obtained with the LB-M9 combination, it leads to a significantly higher curcumin production in the first 24 h of fermentation. This study allowed obtaining the highest concentrations of curcumin reported so far in a heterologous organism and is of interest for all of those working with the heterologous production of curcuminoids, other complex polyphenolic compounds or plant secondary metabolites.